2011
DOI: 10.1007/s10654-011-9565-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-sensitive proteins and risk of atrial fibrillation: a population-based cohort study

Abstract: Low-grade inflammation has been repeatedly associated with cardiovascular diseases but the relationship with incidence of atrial fibrillation (AF) remains unclear. We explored the association between elevated plasma levels of inflammation-sensitive proteins (ISPs) and incidence of AF in a population-based cohort.Plasma levels of five ISPs (fibrinogen, haptoglobin, ceruloplasmin, α 1 -antitrypsin and orosomucoid) and two complement factors (C3 and C4) were measured in 6031 men (mean age 46.8 years) without hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The participation rate was 71%. As a part of the programme, plasma levels of ceruloplasmin were determined for a random sample of 6455 men . Of these men, 3907 were later re‐examined in follow‐up studies including DNA sampling ; the mean age at baseline was 46.3 ± 3.6 years.…”
Section: Methodsmentioning
confidence: 99%
“…The participation rate was 71%. As a part of the programme, plasma levels of ceruloplasmin were determined for a random sample of 6455 men . Of these men, 3907 were later re‐examined in follow‐up studies including DNA sampling ; the mean age at baseline was 46.3 ± 3.6 years.…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory process is considered to be one of the mechanisms for the genesis of cardiac arrhythmias [20,21]. In this study, adipocytokines derived from both epicardial and limb fat tissues significantly decreased I K in H9c2 cells, and the degree of suppression of I K was significantly more prominent with adipocytokines from pericardial than with those from limb fat tissues.…”
Section: Discussionmentioning
confidence: 54%
“…Known markers of inflammation, such as haptoglobin and SAA, were among the proteins identified. Studies from the Malmö Preventive Study, Sweden, have shown that elevated plasma levels of haptoglobin are a risk factor for MI [19]. Recently, Devaux's group identified haptoglobin as a potential biomarker of prognosis of heart failure in patients with acute MI [20].…”
Section: Discussionmentioning
confidence: 99%